Evaluation of nitric oxide metabolism and malondialdehyde levels as an indicator of oxidant stress in malign and parapneumonic pleural effusion - Koyuncu, Pınar; Koyuncu, Adem; Elgün, Serenay (Journal of Surgery and Medicine, 2021)
Background/Aim: Pleural effusion is an important pathology which usually develops comorbid to varying diseases and negatively affects the quality of life. Studies to understand the etiopathogenesis of the disease are important. Although there are some studies in the literature about the arginine-NO metabolism in pleural diseases, there is not another study including all patient groups and the parameters examined in this study. Pleural fluid arginase and NOS (nitric oxide synthase) activities as well as NO (nitric oxide) and MDA (malondialdehyde) levels of patients were determined. The aim of our study was to investigate the possible relationship between these parameters and the mechanism of pleural fluid accumulation. Methods: In this study, pleural fluid arginase and NOS (nitric oxide synthase) activities as well as NO (nitric oxide) and MDA (malondialdehyde) levels of patients with malignancy, pneumonia and CHF (congestive heart failure) were determined. Our study was a cross-sectional descriptive research and our study groups consisted of patients with pneumonia (n=28), malignancy (n=28) and CHF (n=24). NO and MDA level with arginase and NOS activity were determined spectrophotometrically. Results were expressed as mean (standard deviation). Results: Pleural fluid arginase activity in CHF patients was significantly lower than in the malignancy and pneumonia groups (P=0.003). The pleural NO level and NOS activity were higher in the malignancy group than in the other groups (P<0.001). Compared to the other groups, MDA level was significantly increased in the pneumonia group. (P<0.001). Conclusion: In the light of these results, it may be concluded that the arginase- NO metabolism and MDA formation are involved in the pathogenesis of pleural effusions.